1999
DOI: 10.1046/j.1464-410x.1999.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgens on the expression of nitric oxide synthase mRNAs in rat corpus cavernosum

Abstract: Androgens enhance nNOS gene expression in the penile corpus cavernosum of rats, suggesting that they play an important role in maintaining NOS activity. Of the two androgens, DHT was more potent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 30 publications
6
82
1
2
Order By: Relevance
“…Further support for these observations came from recent studies on the relationship between testosterone supplementation and erectile dysfunction (ED). [16][17][18][19] Until the last decade such evidence was unclear; the role of androgen supplementation in sexual function was believed to be derived from its effect on sexual interest and libido. 16 Furthermore, experimental animal and human studies have demonstrated that androgens, primarily testosterone, play an important role in the vasculature of the corpus cavernosum of the penis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further support for these observations came from recent studies on the relationship between testosterone supplementation and erectile dysfunction (ED). [16][17][18][19] Until the last decade such evidence was unclear; the role of androgen supplementation in sexual function was believed to be derived from its effect on sexual interest and libido. 16 Furthermore, experimental animal and human studies have demonstrated that androgens, primarily testosterone, play an important role in the vasculature of the corpus cavernosum of the penis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies in the rat and rabbit have demonstrated a variety of biochemical changes in erectile function and structure that depend on adequate androgen levels. [17][18][19] In humans, the effects of testosterone supplementation have been studied in hypogonadal men with ED. 20 In 15 men with severe hypogonadism and a control group of 20 men with psychogenic ED, testosterone treatment for 6 months with a 5 mg/day patch normalized nocturnal penile tumescence parameters and improved penile vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experimental studies had clearly demonstrated that androgens have important functions in the intrapenile mechanism, by modulating the synthesis and action of neurotransmitters that normally influence the contraction and relaxation states of the smooth muscle cells in the erectile tissues. [4][5][6][7] For those who were not responsive to sildenafil alone and testosterone alone, combined use of sildenafil and testosterone resulted in 12 of the remaining 21 patients regaining a satisfactory erection, which suggests androgen replacement normalized the hormonal milieu that is essential for the action of PDE-5 inhibitor. Shabsigh et al 9 also reported that androgens influence PDE-5's expression and activity in the corpus cavernosum, so androgen supplementation enhances the therapeutic effects of the PDE-5 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…2 Animal and human studies have shown that the expression of the nitric oxide synthase (NOS) gene inside the penis depends on the presence of adequate androgen levels. 3,4 Testosterone also has a permissive role in erectile function, which is not exclusively NO-dependent and induces acute (nongenomic) vasorelaxation via K þ channel activation of vascular smooth muscle cells. 5 Castration, besides leading to reduced NOS expression, also appeared to modify phosphodiesterase type-5 (PDE-5) gene expression in a rabbit model.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO) mediates relaxation of the vascular smooth muscle of the resistance arteries of the corpus cavernosum and the trabeculae to facilitate penile erection. A preponderance of evidence supports a role for androgens in regulating the expression and activity of NOS isoforms in the corpus cavernosum in animal models [14][15][16][17][18][19][20][21][22][23][24][25]. In castrated animals, testosterone or 5α-dihydrotestosterone (DHT) administration restored the erectile response and NOS expression in the penis [9][10][11]16,18,19,21,23,24].…”
Section: Testosterone Regulates Nitric Oxide Synthase Expression and mentioning
confidence: 99%